2010
DOI: 10.1038/aps.2009.206
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine and taurine synergistically inhibit the proliferation and osteoblastic differentiation of vascular smooth muscle cells

Abstract: Aim: To investigate the synergistic action of L-carnitine (LC) and taurine (TAU) on the proliferation and osteoblastic differentiation of vascular smooth muscle cells (VSMCs). Methods: DNA and protein synthesis of VSMCs were assessed using scintillation counting. Alkaline phosphatase (ALP) activity and calcium content were determined to investigate the effects of LC and TAU on the osteoblastic differentiation and mineralization of VSMCs. TAU uptake by VSMCs was assayed. RNA interference was used to down-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In this study, we found that the 10 μM LC positively affected osteoblast proliferation, but the higher concentration of LC (100 μM) slightly decreased osteoblast proliferation compared with the control. Meanwhile, it has recently been demonstrated that supplementation of LC lead to an activation of the IGF-1/PI3K/Akt signalling pathway (46). Therefore, we investigated whether the effect of LC on proliferation and osteoblast differentiation could be mediated by the IGF-1/PI3K/Akt signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the 10 μM LC positively affected osteoblast proliferation, but the higher concentration of LC (100 μM) slightly decreased osteoblast proliferation compared with the control. Meanwhile, it has recently been demonstrated that supplementation of LC lead to an activation of the IGF-1/PI3K/Akt signalling pathway (46). Therefore, we investigated whether the effect of LC on proliferation and osteoblast differentiation could be mediated by the IGF-1/PI3K/Akt signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Since these cells concentrate high amounts of skeletal muscle's taurine (Lobo et al, 2000), a taurine deficiency would presumably affect their regenerative and myogenic functions. In addition, taurine inhibits the differentiation of vascular smooth muscle cells, which also contain high amounts of taurine (Lobo et al, 2000) into collagen-producing osteoblasts (Liao et al, 2008;Xie et al, 2010). Such hypotheses could provide a mechanism through which taurine deficiency inhibits growth in fish.…”
Section: Filet Compositionmentioning
confidence: 99%
“…However, opposite effects of taurine on cell growth have also been reported; taurine can sometimes function as an inhibitor of cell growth (694697), which may probably be explained by its role also as some kind of signal substance inhibiting the growth of certain cell types via receptors located either at the cell surface or inside, perhaps even including nuclear receptors. A more unspecific mechanism caused by its antioxidant effect (and leading to reduced activation of oxidatively regulated signal pathways involving proteins that function as positive regulators of cell growth) can, however, not be excluded, since several different cell surface receptor-associated proteins, protein kinases, protein phosphatases and transcription factors are known which are either directly or indirectly (via proteins that are upstream in the signal pathway) redox-regulated, and which are known to be of crucial importance either for cellular growth regulation or the regulation of apoptosis (so that stimulation of the signal pathways concerned will lead to enhancement of the rate of cell growth and/or suppression of cell death by apoptosis).…”
Section: Functions Of Taurine As An Osmolyte and As A Growth Factor Tmentioning
confidence: 99%
“…Since taurine has been reported to inhibit the growth of cell types such as fibroblasts (695) and vascular smooth muscle cells (694, 697), it might be speculated that taurine supplementation could be helpful in some of those diseases where fibrosis and/or smooth muscle hypertrophy are important parts of the disease process, as in chronic obstructive pulmonary disease (COPD), alcoholic liver disease and other poison-induced fibrosis (in the liver or elsewhere), arteriosclerosis (in which patient group other cardiovascular protective effects of taurine also might be highly relevant), fibrosis in parts of the skeletomuscular apparatus leading to impaired mobility (with fibrosis prevention potentially being a positive side effect if taurine is used regularly for treatment of muscular or joint pains), and fibrosis as a side effect of radiation therapy.…”
Section: Functions Of Taurine As An Osmolyte and As A Growth Factor Tmentioning
confidence: 99%